Treating people well : the extraordinary power of civility at work and in life - Berman, Lea; Bernard, Jeremy (Scribner, 2018)
A guide to personal and professional empowerment through civility and social skills, written by two White House Social Secretaries who offer an important fundamental messageeveryone is important and everyone deserves to be treated well.--Provided by Publisher.